Structural and functional properties of OSA-starches made with wide-ranging hydrolysis approaches. (May 2019) - Han, Huaxin; Zhang, Haixiang; Li, Enpeng; Li, Cheng; Wu, Peng
Abstract: Octenyl succinic anhydride modified starches (OSA-starches) are widely used as emulsifiers and stabilizers in the food industry. This study investigates the relationships between molecular structure and emulsifying and antioxidant properties of OSA-starches with a wide range of structures, formed by hydrolysis by α -amylase, β -amylase and HCl for various hydrolysis times. Structural parameters, namely molecular size distribution, chain-length distribution, degree of branching (DB) and degree of OSA substitution (DS) were characterized using size-exclusion chromatography and 1 H nuclear magnetic resonance. These parameters were then correlated with viscosity, emulsification performance and antioxidant properties for OSA-stabilized oil emulsions, to gain improved understanding of structure-property relationships. The average chain length (DP) and DB respectively showed positive and negative correlations with the viscosity, total antioxidant activity (TAC), creaming extent and the emulsion z-average droplet size for all the hydrolyzed samples. The OSA-starches treated by α -amylase generally had the smallest average DP and largest DB, resulting in the lowest viscosity and the best droplet stability with the smallest creaming extent. The acid-hydrolyzed OSA-starch samples presented larger average DP than the enzyme-hydrolyzed samples, in agreement with their better TAC, while larger creaming extent. The β -amylase-hydrolyzed samples produced moderate structural degradation and emulsifying properties compared to the OSA-starches treated by α -amylase and HCl. The structure-property correlations indicate that the average chain length and DB are the two most important structural parameters in determination of the functional properties for the OSA-modified starches. These findings will help develop improved food additives with desired functions. Graphical abstract: Image 1 Highlights: Average DP positively correlated with viscosity, TAC and emulsion droplet size. DP and DB of OSA-starches are the two key factors determining functional properties. α-amylase-hydrolyzed OSA-starches had lowest viscosity and best droplet stability. Acid-hydrolyzed OSA-starches presented better TAC while lower droplet stability. β -amylase hydrolysis produced moderate structural degradation and emulsifying properties.